2009
DOI: 10.1002/ibd.20733
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of experimental colitis in mice by CD11c+ dendritic cells

Abstract: This study demonstrates that resident DCs can suppress the severity of acute DSS colitis and that regulation of IL-6 production may contribute to DC-mediated control of intestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 88 publications
(118 reference statements)
1
49
0
Order By: Relevance
“…Enhanced DC efferocytosis, due to the lack of CD300f, induced DCs to overproduce TNF-α, which stimulated the production of additional proinflammatory cytokines, particularly IFN-γ, by lamina propria T cells. Accumulation of activated DCs has been observed at the inflamed sites in colons of human IBD patients and mice with experimentally induced colitis (40), with no clear indication as to their role in the disease pathogenesis (30,41). Our data indicate that dysregulation of DC efferocytosis may contribute to chronic gut inflammation.…”
Section: Cd300fmentioning
confidence: 70%
“…Enhanced DC efferocytosis, due to the lack of CD300f, induced DCs to overproduce TNF-α, which stimulated the production of additional proinflammatory cytokines, particularly IFN-γ, by lamina propria T cells. Accumulation of activated DCs has been observed at the inflamed sites in colons of human IBD patients and mice with experimentally induced colitis (40), with no clear indication as to their role in the disease pathogenesis (30,41). Our data indicate that dysregulation of DC efferocytosis may contribute to chronic gut inflammation.…”
Section: Cd300fmentioning
confidence: 70%
“…At present study, MPO levels which reflect the degree of neutrophils influx into tissues (26), of buccal mucosa on D7 and D30 were compared for confirming the different influx of neutrophils. It was found that MPO level of X-D7 group was significantly higher than that of on D30 and this higher MPO level could be attenuated by the treatment of immunosuppressant FK506.…”
Section: Discussionmentioning
confidence: 80%
“…When mice are pretreated with immunostimulatory DNA sequences before DSS administration, the presence of DCs is protective, partly because of type I IFN release that regulates the recruitment of neutrophils and monocytes and their inflammatory activities in the inflamed colon (62). Conversely, if DCs are ablated before DSS treatment, colitis is exacerbated (63), which suggests that DCs play a protective role in the initial phases of colitis but play a pathogenic role at a later time in disease course. There might be several mechanisms by which resident DCs could protect the colon during the initiation of colitis, but their ability to induce Treg development may play a primary role.…”
Section: Dcs In Intestinal Diseasementioning
confidence: 99%